Study of the aesthetic concepts of Suhrawardi's illumination in Iranian traditional Music - Reza Azizia, Mohammad; Saraei, Pouya; Yazdi, Hossein (International Journal of Psychosocial Rehabilitation, 2020)
The Iranian-Islamic wisdom of Suhrawardi's Illumination, can be a basis for examining the subject of ruling in traditional arts. The purpose of this study was to answer the question of what are the aesthetic concepts of Suhrawardi’s illumination wisdom and how do they appear in Iranian traditional music? The method of this research was applied theoretical in terms of purpose and descriptive-analytical in terms of method of implementation. The information was obtained through library methods. The results show that Suhrawardi's illumination Philosophy, which begins with a critique of Mashay’s thought, uses new concepts and innovations to explain and formulate the hierarchy of the world's existential and cognitive hierarchy. Based on this philosophy on Illumination and the emergence of existence, conditioning life and existence and its perception, on the emergence and light, the function of imagination as an intermediary and the creation of suspended forms based on the tests of fixed motifs of the kingdom, pleasure and innovation resulting from the perception of images in the world. The example and revelations of the realms of the kingdom and its inclusion in the memory of the seeker have given the illumination thought an aesthetic and artistic form. The concepts of Illumination philosophy have been manifested as content in Iranian music, and this art in the position of the face are the manifestation of the concepts of Illumination philosophy. This two-way relationship suggests that there are precise concepts behind artistic forms, which are the reasons for the formation of structure and examples in the field of Iranian music, in other words, the language that expresses these concepts.